The Significance of Artificial Neural Networks in Educational Research A Summary of Research and Literature - Duykuluoglu, Ayhan (Technium BioChemMed, 2021)
Today based on the improvements in computer technologies, research aims at developing new ways of processing data. Some research focus on creating new instruments which imitate the biological data processing mechanisms of human beings. These kinds of research have paved the way for the development of artificial neural networks which can be regarded to be a superior tool for predictive analysis when compared to the traditional and more commonly applied predictive analysis tools. Today artificial neural networks have gained widespread applications in such disciplines as ecology, engineering and health. However, it can be alleged that they have been confined to limited application in educational research though they could be more functional and effective than other predictive analysis. This study aims at shedding light on the functionality and the role which artificial neural networks can fulfill in educational research by referring to the studies which were carried out through articial neural networks analysis.